Magnetic resonance imaging with intravenous gadoteridol injection based on 3D-real IR sequence of the inner ear in Meniere's disease patient: feasibility in 3.5-h time interval. (1st October 2021) - Chen, Wei; Geng, Yue; Lin, Naier; Yu, Sihui; Sha, Yan
Abstract: Background: Intravenous gadoteridol injection can be applied to visualize endolymphatic hydrops (EH). Aims/objectives: To explore whether 3.5-h time interval was feasible for clinical practice. Materials and methods: We collected 70 unilateral Meniere's disease (MD) patients who were divided into two groups randomly (group A: 3.5-h time interval; group B: 4-h time interval). Among the two groups, the signal intensity (SI) in perilymphatic area of the basal turn of cochlea, the results of visual evaluations in the vestibule, cochlea and semicircular canal and the detection results of EH were compared. Results: Regarding the SI, no difference was found between A-affected ears and B-affected ears ( p =.499), and no difference was found between A-unaffected ears and B-unaffected ears ( p =.111). However, a difference was found between A-affected ears and A-unaffected ears ( p =.005), and a difference was found between B-affected ears and B-unaffected ears ( p =.012). Besides, no difference was found between the visual evaluations in the vestibule, cochlea, and semicircular canal of the two groups. Regarding the detection results of EH, no difference was found between the two groups (all p >.05). Conclusions and significance: In the clinical application of gadoteridol for the inner ear, 3.5-h delayed MR imaging is feasible.